Kasus Peralihan Status Sertifikat Hak Pakai Barang Milik Daerah Bengkulu Berubah Menjadi SHGB Mega Mall - Regyta Cahyani; Regita Merlandri; Vinda Milsyi Almeira; Jojor Cristina; IndriManalu . (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Issues regarding the management of land originating from Regional Property (BMD) often create legal conflicts if there are changes in land rights status not according to agrarian law provisions. One case attracting public attention is the status transfer of Bengkulu Mega Mall land from Right to Manage (HPL) or regional property use rights to Building Use Rights Certificate (SHGB). This change raises legal issues, including alleged corruption and state financial losses. This study aims to analyze the land status transfer based on the Indonesian agrarian law perspective. The research method used is normative legal research with statute and case approaches. The results indicate that the land status change is suspected not fully compliant with land law provisions, particularly regarding the relationship between HPL and HGB. Furthermore, land management by private parties without clear contributions to the local government contradicts the principle of the social function of land in the Basic Agrarian Law.